The pleasurable lightness of being: Interface, mediation and meta-narrative in Lucasfilm's Loom - Jaroslav Švelch (Eludamos, 2009)
This critique of the overlooked Lucasfilm adventure game focuses on the techniques, by which the distance between the avatar and the player is bridged, and the way the game deals with its gameness in its fiction.